Characterization of biosafety vertical public cemetery located in Santa Barbara (Minas Gerais) (Research, Society and Development, 2020)
The most widely used form of burial since the Middle Ages are traditional cemeteries which, in addition to demanding extensive areas for burial of bodies, consist of potential sources of pollution, given the presence of necrochorume. In this context, aiming to eliminate the problems associated with the scarcity of physical space verified in the traditional cemetery, a biosecurity vertical cemetery was implanted in the municipality of Santa Barbara (MG). Thus, this work aimed to characterize this model of burial and to evaluate the relationship between vertical and horizontal cemeteries. The methodology used was the analysis of documents related to the construction and operation of horizontal and vertical cemeteries, as well as field research to observe the operation of the system associated with the biosecurity vertical cemetery. It was noted that the vertical cemetery uses ecological materials for the manufacture of locules, tombstones and ossuary urns, which do not allow the passage of gases or leakage of liquids from the decomposition of bodies. In addition, the biosecurity vertical cemetery has a central for the treatment of gases involving the absorption, dissociation and adsorption steps, returning them to the environment again without odors. It is noteworthy that with the implementation of the vertical cemetery model, the useful life of the space was extended to over 50 years, and in the traditional model the service life was at most 2 years. Finally, it is necessary to search for new technologies that minimize the negative environmental impacts triggered by cemeteries.